The psychological characteristics of peak performance in Taiwanese Olympic athletes: a qualitative study - Chi, L.; Chien, T. H.; Lei, C. Y.; Wen, T. Y.; Chen, J. Y.; Hung, H. W. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
Introduction The peak performance of athletes has always been expected to appear frequently by coaches and players and to clearly understand the nature, appearance, and development control strategies. Gardner (2009) suggests that the studies of athletes` peak performance can help athletes to achieve and maintain the feeling of `in the zone` and the state of idea performance. In the past, most of the research on the psychological state of peak performance`s data was studied by athletes in Western countries. In addition, only few studies recruited Olympic athletes as participants. The psychological state of athletes peak performance might be affected by different competitive levels and cultures, so it is necessary to establish local data to understand the psychological state and characteristics of peak performance of elite athletes in Taiwan, and then provide a basis for subsequent assistance in athletes psychological skills training.